Improved solubility and bioavailability of cyclolinopeptides by diacylglycerol in the β-cyclodextrin Pickering emulsions - Liu, Zhongbo; Lee, Yee Ying; Tan, Chin Ping; Wang, Yong; Qiu, Chaoying (Elsevier Ltd, 2025)
Cyclolinopeptides (CLs) have anti-inflammatory, anti-osteoporosis, and anti-tumor effects, however, low water and oil solubility greatly limit their application. Herein, CLs-loaded β-cyclodextrin (β-CD) emulsions were prepared with different oil phases. The in vitro digestibility, cellular absorption, and anti-inflammatory effects were evaluated. Camellia oil diacylglycerol (CO DAG) showed enhanced dissolving ability for CLs due to high polarity. β-CD formed inclusion complexes with DAG through hydrogen bond and the emulsions showed smaller size and higher physical stability with 50 % (w/w) oil. The in vitro digestibility of the DAG emulsion was increased and the CLs' bioavailability was 13.6–fold higher than CLs in oil. The CLs–loaded Pickering emulsion digesta exhibited a higher nitric oxides (NO) inhibition rate (58.62 %) and Caco-2 cell penetration (3.09 × 10−6 cm/s). Therefore, emulsion formulated with β-cyclodextrin and DAG can effectively improve the solubility and bioavailability of CLs, which has significant potential for application in functional foods and pharmaceutical industry.